Determining the Optimum Training Conditions for Selective Strengthening of Vastus Medialis Oblique Muscle over Vastus Lateralis through Using Musculoskeletal Modeling - Farzam Farahmand; Seyyed Hosein Hoseini; Mohamad Mahdi Seifi (Islamic Azad University, Hamedan Branch, 2016)
Objective: The purpose of this study is to find the optimum training conditions for selective strengthening of the vastus medialis oblique muscle over vastus lateralis. Methods: For this purpose, a musculoskeletal model of lower limb was developed by OpenSim software. Using a detailed tibiofemoral and patellofemoral joint modeling and six muscular branches for components of quadriceps femoris muscle on the other hand, training conditions were simulated in isometric, isokinetic and isotonic modes. For each training condition, the motion kinematic and external force was applied to the model. After analyzing the inverse dynamics, the force of each component of quadriceps femoris muscle was obtained through the statical optimization. Impact of knee angle, speed of movement, external loading level and axial tibial rotation on activity rate of vastus medialis oblique to vastus lateralis muscle was investigated based on the model. Results: The results showed that the knee angle affect on this ratio and the highest ratio could be obtained in angles close to full extension of knee. Speed of movement and external load level would not affect the ratio. Meanwhile axial tibial rotation could affect this ratio in a way that increasing tibial external rotation was associated with increasing the ratio. Conclusion: The results indicate that high-speed isokinetic training with highest levels of tibial external rotation in angles close to full extension of knee can resulte in increasing the maximum activity ratio of vastus medialis oblique to vastus lateralis muscle.